A "Distorted‐BODIPY"‐Based Fluorescent Probe for Imaging of Cellular Viscosity in Live Cells1. Issue 16 (5th March 2014) - Zhu, Hao; Fan, Jiangli; Li, Miao; Cao, Jianfang; Wang, Jingyun; Peng, Xiaojun
Abstract Cellular viscosity is a critical factor in governing diffusion‐mediated cellular processes and is linked to a number of diseases and pathologies. Fluorescent molecular rotors (FMRs) have recently been developed to determine viscosity in solutions or biological fluid. Herein, we report a "distorted‐BODIPY"‐based probe BV‐1 for cellular viscosity, which is different from the conventional "pure rotors". In BV‐1, the internal steric hindrance between the meso‐CHO group and the 1, 7‐dimethyl group forced the boron–dipyrrin framework to be distorted, which mainly caused nonradiative deactivation in low‐viscosity environment. BV‐1 gave high sensitivity (x=0.62) together with stringent selectivity to viscosity, thus enabling viscosity mapping in live cells. Significantly, the increase of cytoplasmic viscosity during apoptosis was observed by BV‐1 in real time.